ASSISTANCE OFASSIGNED TEACHERS ON THE ACHIEVEMENT OF TPQ STUDENTS AT THE GUNUNG PANDAK ISLAMIC BOARDING SCHOOL, MALANG PERFORMANCE - Muhammad Husni (Salwatuna, 2022)
Abstract Tahfidzul qur'an and Tartil qur'an competitions are a type of competition at the TPQ level and Formal institutions organized by the Branch Leader of Muhammadiyah Tempur Donomulyo Malang. The competition was held in the month of Ramadan, with various delegates from other institutions including 76 institutions that took part in the contest with 500 participants, both tahfidz and tartil participants. The teacher assigned to be a pioneer in the victory event for the students of TPQ Gunung Pandak Malang, namely by applying the CBSA learning model as a form of the method he used. This study aims to determine the application of the CBSA learning model, namely the active student learning method, which means active student learning design, namely students are more active in learning than their teachers. So the teacher here only reprimands and corrects the student's mistakes in the material he is studying. The results of this study describe the success of students in the learning model using the CBSA model. The method used in this study is the CBSA method, which is an active student learning method, unlike other methods, CBSA is a simple method but affects student success. Assignment teacher as a motivation for students in reaping the success of a competition.